2020
DOI: 10.1155/2020/1425402
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and In Vitro and In Vivo Evaluations of Cellulose Hydrogels Enriched with Larrea tridentata for Regenerative Applications

Abstract: Introduction. Tissue engineering is an elementary necessity for several applications in the biomedical field through the use of several biopolymers derived from plants. Larrea tridentata (LT) is a very used plant for various medicinal applications with interesting properties; however, its use into cellulose hydrogels for possible regenerative therapeutics is still limited. Cellulose films could be applied in medical field as wound healing, scaffold for connective tissue for periodontal applications, and so on.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several studies have reported the pharmacological properties of Larrea tridentata, such as antioxidant [19][20][21][22][23][24][25], antitumoral [23], neuroprotective [26,27], regenerative [28], hepatoprotective [29][30][31], nephroprotective [32,33], antiviral [34], antifungal (mainly against fungi associated with agricultural crops, including tomatoes) [22,[35][36][37][38], antiparasitic [39], and antibacterial (against Gram-positive and Gram-negative bacteria and Mycobacteria) effects [40][41][42][43][44][45][46][47][48][49]. However, there are no reports on the antibacterial activity of this plant against pathogens that affect agricultural production, so the aim of the present study was to evaluate the antibacterial activity of hydroalcoholic extract and fractions of Larrea tridentata against phytopathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the pharmacological properties of Larrea tridentata, such as antioxidant [19][20][21][22][23][24][25], antitumoral [23], neuroprotective [26,27], regenerative [28], hepatoprotective [29][30][31], nephroprotective [32,33], antiviral [34], antifungal (mainly against fungi associated with agricultural crops, including tomatoes) [22,[35][36][37][38], antiparasitic [39], and antibacterial (against Gram-positive and Gram-negative bacteria and Mycobacteria) effects [40][41][42][43][44][45][46][47][48][49]. However, there are no reports on the antibacterial activity of this plant against pathogens that affect agricultural production, so the aim of the present study was to evaluate the antibacterial activity of hydroalcoholic extract and fractions of Larrea tridentata against phytopathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Tovar-Carrillo et al (2020) analyzed the compatibility of the in vitro and in vivo properties of cellulose hydrogels enriched with L. tridentata that had been implanted intramuscularly in female rats. At the end of the in vivo assay (90 days), no evidence of inflammation, toxicity or death was observed; furthermore, it was observed that the addition of L. tridentata improved cytocompatibility, demonstrating that enriched hydrogels can be used as regenerative scaffolds [ 40 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%